The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.5194/amt-6-2577-2013
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of desert dust aerosol vertical profiles from IASI measurements in the TIR atmospheric window

Abstract: Abstract. Desert dust aerosols are the most prominent tropospheric aerosols, playing an important role in the earth's climate. However, their radiative forcing is currently not known with sufficient precision to even determine its sign. The sources of uncertainty are multiple, one of them being a poor characterisation of the dust aerosol's vertical profile on a global scale. In this work, we tackle this scientific issue by designing a method for retrieving dust aerosol vertical profiles from Thermal Infrared m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 51 publications
1
65
0
Order By: Relevance
“…In solar occultation, dust and clouds will mostly reduce the level of sunlight reaching the instrument by extinction, whereas in nadir observations, the situation is more complex and depends highly on the optical properties (single scattering albedo, phase functions) governing the interaction of light and the aerosols. All the simulations in nadir shown here were obtained using a full scattering scheme adapted to Martian conditions (Drummond et al 2011;Vandenbussche et al 2013). The model includes Rayleigh scattering and aerosol properties (i.e.…”
Section: Expected Performancementioning
confidence: 99%
“…In solar occultation, dust and clouds will mostly reduce the level of sunlight reaching the instrument by extinction, whereas in nadir observations, the situation is more complex and depends highly on the optical properties (single scattering albedo, phase functions) governing the interaction of light and the aerosols. All the simulations in nadir shown here were obtained using a full scattering scheme adapted to Martian conditions (Drummond et al 2011;Vandenbussche et al 2013). The model includes Rayleigh scattering and aerosol properties (i.e.…”
Section: Expected Performancementioning
confidence: 99%
“…A best-guess estimate would be that the uncertainty is of the order of 1-1.5 km. Vandenbussche et al (2013) found that for low dust loads, the BIRA-IASB algorithm placed the aerosol layer 1-2 km above the CALIOP-retrieved layer. The algorithm has since undergone several revisions and improvements and the average overestimate for all data is 0.078 km (0.590 km) when compared with the CALIOP geometric mean (cumulative extinction) height.…”
Section: Discussionmentioning
confidence: 99%
“…The various dust height retrieval algorithms used in this study are summarized in Table 1 and described in more detail below. Peyridieu et al (2010Peyridieu et al ( , 2013, from Volz (1972Volz ( , 1973 layer height Capelle et al (2014) The Mineral Aerosol Profiling from Thermal Infrared (MAPIR) retrieval algorithm is an extensive technical and scientific improvement of the algorithm first published by Vandenbussche et al (2013). Version 3.5 of the algorithm, fully described in Vandenbussche and De Mazière (2017), is used in this study.…”
Section: Passive Instrument Dust Height Retrievalsmentioning
confidence: 99%
See 2 more Smart Citations